GEOTHERMAL POTENTIAL IDENTIFICATION BASED ON REMOTE SENSING ANALYSIS IN IJEN GEOTHERMAL FIELD, EAST JAVA - Fauzi, Ridwan Nur; Patonah, Aton; Pratiwi, Santi Dwi; Hirose, Kazuyo; Rendra, Pradnya Paramarta Raditya (Fakultas Teknik Geologi Universitas Padjadjaran, 2023)
Geothermal is a renewable energy resource that is used for various needs, both as heat energy on a local scale to electricity production on an industrial scale. The search for geothermal resources is difficult and costly, thus a survey method is needed that can facilitate the geothermal exploration stage in a large area coverage. Remote sensing methods can be an adequate tool to guide investigations of geothermal prospect areas through the elaboration of potential hydrothermal resource maps at the level of profitable potential zones for exploitation. The purpose of this study is to identify areas that support geothermal exploration and exploitation in the Ijen Mountains area, East Java. The method used includes processing OLI (Operational Land Imager) and TIRS (Thermal Infrared Sensor) sensor images from the Landsat-8 satellite to obtain the distribution of hydrothermal alteration zones and surface temperature anomalies. Identification of permeable zones based on fracture density in the study area was also carried out by analyzing Digital Elevation Model (DEM) data to obtain the topographical features of the study area. The results of the study show that there is a correlation between the parameters used in several areas which are then interpreted as geothermal prospect zones. The moderate to high prospect zone was found to be associated with most of the known presence of geothermal manifestations.